Descriptive Study: The Lexicon Used in The Makepung Tradition by The People of Jembrana Regency - Darmawan, Putu Wahyu Edi (Universitas Pendidikan Ganesha, 2023)
The development of science and technology has caused local traditions to be abandoned by the younger generation, one of which is the Makepung tradition. To preserve this culture, it is necessary to conduct an in-depth study regarding the lexsicon elements in this tradition. This study aimed to describe and analyze the lexicon that was used on the Makepung tradition in Kaliakah village, Jembrana Regency. This study was designed in the form of descriptive qualitative study and used eco-linguistic approach. There were two process in collecting the data in this study, namely, observation and interview with the informan. Three informants were chosen based on the standard requirement and criteria determined in this study. The data were analyzing based on the data obtained from the informants and described descriptively. Based on the data analysis that have been conducted in this study, it was found that there were total 54 lexicons that is listed in this study, those lexicons are some terms that is commonly used in the Makepung tradition in Kaliakah village, Jembrana Regency. It was expected that this study can be a reference for the other researchers who have interest in Eco-linguistics study, especially for the makepung tradition of Jembrana regency.